2014
DOI: 10.13005/ojc/300143
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Synthesis of 2,4,5-Triaryl-1H-Imidazole Derivatives using SiO2-NaHSO4 under Solvent-free Conditions

Abstract: A mixture of benzyl, aromatic aldehyde and ammonium acetate in presence of SiO 2 -NaHSO 4 under solvent-free condition were converted to 2,4,5-Triaryl-1H-Imidazoles. The short reaction time, cleaner reaction, and easy workup make this protocol practical and economically attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Comparisons of efficacy of CuB 4 O 7 with those of the reported catalysts 70–91 for the synthesis of 2,4,5-trisubstituted imidazole have shown that the present system involving CuB 4 O 7 has proven to be more efficient in terms of the short reaction time, milder reaction condition, and product yields (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…Comparisons of efficacy of CuB 4 O 7 with those of the reported catalysts 70–91 for the synthesis of 2,4,5-trisubstituted imidazole have shown that the present system involving CuB 4 O 7 has proven to be more efficient in terms of the short reaction time, milder reaction condition, and product yields (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…30(1), 355-357 (2014) Although numerous methods are capable of affecting these synthesis has been previously reported [9][10][11][12][13][14][15][16][17][18] . Previously, we have synthesized a number of heterocyclic compounds [19][20][21][22][23][24][25][26][27][28][29][30] . Herein we report some of DHPMs at one pot reaction, environmentally friendly with high yields and easy separation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several improved methodologies have been developed that use triethylbenzyl ammonium chloride 10 , p-dodecyl benzenesulfonic acid 11 , phosphomolybdic acid supported on silica gel 12 , sulfonic acid on silica gel 13 , HClO 4 -SiO 2 14 and ZnO 15 among others. Previously, we have synthesized a number of heterocyclic compounds [16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%